Pengenalan Dan Pelatihan Proses Pembuatan Balsam Cair Di Gampong Lubok Sukon Kecamatan Ingin Jaya, Kabupaten Aceh Besar - Sofyana, Sofyana; Mairiza, Lia; Razi, Fachrul; Mulana, Farid; Suriaini, Nanda (Universitas Syiah Kuala, 2024)
This training activity aims to enhance the knowledge, insights, and skills of the community regarding external medicines, specifically the skills to make liquid balm that is beneficial for health. Additionally, this activity aims to foster entrepreneurial interest among the community through home-based businesses that can increase family income. The activity is centered in Lubuk Sukon Village, Ingin Jaya District, Aceh Besar Regency. The targets of this training activity are housewives and teenage girls who spend most of their time taking care of their households and families. To facilitate this training activity, brochures about the materials and procedures for making balm, the ingredients used, introductory theory, and tips for making balm were distributed to the target community. Furthermore, demonstrations and hands-on practice in making balm were provided, resulting in products that can be used personally or become a business idea.